Effect Of Led Exposure Time On The Temperature Rise, Depth Of Cure And Microhardness Of Nanohybrid Composite Resin - Nauli Komala, Olivia; Budianto, Ednanisa; Kusuma Eriwati, Yosi; Triaminingsih, Siti (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2012)
It has been reported that depth of cure of composite resin can beachieved by prolonged light curing but causing temperature rise that could harmthe pulp and resulted uncomfortable condition to patient. Objectives: To evaluatethe effect of light-emitting-diode (LED) light curing unit on the temperature rise,depth of cure and microhardness of nanohybrid composite resin. Materials andMethods: Sixty specimens of nanohybrid composite resin (Tetric N Ceram,Ivoclar-Vivadent, Lichtenstein) with diameter of 5 mm, thickness of 5 mm weredivided into 3 groups: Group I (n=20) were light-cured for 15 seconds, Group II(n=20) for 20 seconds, Group III (n=20) for 40 seconds using LED light curingunit (Hilux/Ledmax, Japan). The temperature rise was measured using digitalthermometer at initial time to the highest temperature peak. The depth of cure wasmeasured by scraping method. Microhardness was determined using VickersMicrohardness Tester at each 1 mm depth of the composite resin. Data wereanalyzed using Kruskal-Wallis and Mann-Whitney tests. Results: There weresignificant differences on temperature rise, depth of cure and hardness ofnanohybrid composite resin at each 1 mm depth after light exposure time of 15,20, and 40 seconds. The highest depth of cure was achieved after curing for 40seconds but the highest microhardness was achieved after curing for 20 seconds at1 mm from the top of specimens. Conclusion: Exposure time of 20 secondsproduced low temperature rise, depth of cure and the highest VHN than the otherexposure time.